One-dimensional breakdown voltage model of SOI RESURF lateral power device based on lateral linearly graded approximation - 张珺 郭宇锋 徐跃 林宏 杨慧 洪洋 姚佳飞 (Chinese physics B, 2015)
A novel one-dimensional（1D） analytical model is proposed for quantifying the breakdown voltage of a reduced surface field（RESURF） lateral power device fabricated on silicon on an insulator（SOI） substrate.We assume that the charges in the depletion region contribute to the lateral PN junctions along the diagonal of the area shared by the lateral and vertical depletion regions.Based on the assumption,the lateral PN junction behaves as a linearly graded junction,thus resulting in a reduced surface electric field and high breakdown voltage.Using the proposed model,the breakdown voltage as a function of device parameters is investigated and compared with the numerical simulation by the TCAD tools.The analytical results are shown to be in fair agreement with the numerical results.Finally,a new RESURF criterion is derived which offers a useful scheme to optimize the structure parameters.This simple 1D model provides a clear physical insight into the RESURF effect and a new explanation on the improvement in breakdown voltage in an SOI RESURF device.